Some like it hot: Household disagreement and productivity in smallholder chili production in Indonesia - Sayekti, Apri Laila; Gregg, Daniel; Stringer, Randy (National Research and Innovation Agency, Indonesia, 2023)
Women’s leadership of smallholder households is a major component of women’s empowerment. Approaches to understanding women’s empowerment in Southeast Asian countries require nuance due to the lack of independently managed plots by male and female spouses. We present an approach that allows detailed insights into women’s leadership of activities and the extent to which male and female spouses disagree about leadership. Using a 52 BOOK OF ABSTRACTS combination of confirmatory factor analysis and a revenue function regression, we show that female leadership and disagreement are both significant factors affecting household revenues from chili farming in rural Indonesia. In particular, disagreements can diminish chili revenues and act to reverse gains from female leadership. Our results indicate women’s empowerment in these regions is strongly affected by the extent to which households can agree on the importance of women’s leadership. Results indicate a need to consider interventions that support building communication between the spouses and that reinforces the importance of acknowledging women’s roles as leaders in decision-making in the household.